Is survival after sublobar resection vs. lobectomy made equivalent by extent of lymphadenectomy? - Song, Kimberly J.; Flores, Raja M. (Annals of Translational Medicine, 2019)
Mediastinal lymph node sampling versus dissection in the surgical staging of early non-small cell lung cancers (NSCLC) has been a controversial topic (1). In their manuscript “Extent of lymphadenectomy is associated with oncological efficacy of sublobar resection for lung cancer ≤2 cm,” Stiles and colleagues (2) used data from the Surveillance, Epidemiology, and End Results (SEER) database to investigate whether the extent of lymph node dissection affects survival in patients undergoing segmentectomy or wedge resection for early NSCLC.